Prevalence of pregnancy induced hypertension and pregnancy outcomes among women seeking maternity services in Harare, Zimbabwe. Issue 1 (December 2015) - Muti, Monica; Tshimanga, Mufuta; Notion, Gombe; Bangure, Donewell; Chonzi, Prosper
Abstract Background Pregnancy induced hypertension (PIH) is one of the most common causes of both maternal and neonatal morbidity, affecting about 5 – 8 % of pregnant women. It is associated with adverse pregnancy outcomes as well as maternal morbidity and mortality. Harare City experienced an increase in referrals due to PIH to central hospitals from 2009 to 2011. We conducted a study to determine the prevalence of PIH and pregnancy outcomes among women with PIH. Methods An analytic cross sectional study was conducted. Interviewer administered questionnaires were used to capture demographic data, obstetric history and knowledge on PIH management. Records were reviewed for pregnancy outcomes while key informants were also interviewed on patient management. Results PIH prevalence was 19.4 %. Women with PIH were three times more likely to deliver a low birth weight baby (OR 3.00, p = 0.0115), 4.3 times more likely to have still birth (OR 4.34, p = 0.0517) and four times more likely to have a baby with low Apgar score at 5 minutes (OR 4.47, p = 0.0155) compared to women without PIH. There was no statistically significant difference in delivery before 37 weeks gestation between women with PIH and those without (OR 1.70, p = 0.1251). 12, 5 % of the women delivered by caesarean section. Methyldopa was the drug of choice for management of PIH. Less than half of the health workers had sufficient knowledge on definition or management of PIH. Delay in seeking care and shortage of resources were the major reported challenges in the proper management of PIH. Conclusion PIH prevalence was high. Women with PIH were at higher risk of adverse pregnancy outcomes than those without. Poor knowledge of management of PIH and inadequate resources are a threat to the proper management of PIH. This underscores the need for increased human resources and capacity building as well as resource mobilisation for proper management of pregnant women. Urinalysis must be routinely done for all pregnant women regardless of their blood pressure.